Penafsiran Báº£tinÄ (Esoteris) Thabáº£thabáº£âÄ Dalam TafsÄr Al-MÄzáº£n - Kerwanto, Kerwanto (Tanzil : Jurnal Studi Al-Quran, 2016)
Abstract :This paper is a review to Rosihon Anwarâs book titled âMenelusuri Ruang Batin Al-Quran: Belajar Tafsir Batini pada âAlláº£mah Thabáº£thabáº£âá¿â. This study will make a picture of two important themes in this book. The first is about the nature of esoteric interpretations in the view of Thabáº£thabáº£âá¿. The second is Thabáº£thabáº£âá¿âs position toward hadá¿ts that come from Shia Imams in his esoteric interpretations. Furthermore, this paper also intented to criticize some Rosihonâs views. Such as: (1). The periodization birth of Shia esoteric interpretations; (2). Equating of the models of Thabáº£thabáº£âá¿âs esoteric interpretations with Sufiâs; (3). Thabáº£thabáº£âá¿âs position toward hadá¿ts that come from Shia Imams; and (4). Claims that, Thabáº£thabáº£âá¿âs esoteric interpretations violate the context of the word.Â Abstrak :Tulisan ini merupakan kajian ulang (review) terhadap buku karya Rosihon Anwar yang berjudul âMenelusuri Ruang Batin Al-Quran: Belajar Tafsir Batini pada âAlláº£mah Thabáº£thabáº£âá¿â. Kajian ini hendak memotret dua tema penting dalam buku ini, yakni pertama, tentang hakikat tafsir esoterik dalam pandanganÂ  Thabáº£thabáº£âá¿. Kedua, sikap Thabáº£thabáº£âá¿ terhadapÂ  riwayat yang bersumber dari para Imam Syiah dalam penafsiran esoteriknya. Selanjutnya, tulisan ini juga ditujukan untuk mengkritik beberapa pandangan Rosihon, seperti: (1). Periodesasi lahirnya tafsir esoterik Syiah; (2). Penyamaan model tafsir esoterik Thabáº£thabáº£âá¿ Â dengan tafsir esoterik para sufi; (3). Sikap Thabáº£thabáº£âá¿ terhadap riwayat para Imam Syiah; dan (4). klaim bahwa, penafsiran esoterik Thabáº£thabáº£âá¿ menyalahi konteks kata.